Perang Uhud (Suatu Analisis Historis Sebab-Sebab Kekalahan Umat Islam) - Iqbal Iqbal (Rihlah : Jurnal Sejarah dan Kebudayaan, 2014)
This paper explain about Uhud War, an accident was happening on Syawwal 07th, 03 H./625 M. On the war,  two groups were fighting each other,  Moslems and Quraisy Clan.  This paper explain on the  history side and doing on qualitative research type  by  library research. Uhud  War is  the second war after  Badar War. On this  war, Moslem was losing. This drubbing  was happening cause some Moslems wasn’t loyal to prophet’s command. This  accident  made Hamzah died and prophet Muhammad  saw. was hurt by Quraisy Clan. So, Uhud War is the war had been a training for Moslems, including some Moslems supporter had gotten out from Moslem’s line. This group was commanded by Abdullah Bin Ubay. They  were going back to Madinah before the war happened. This accident absolutely made account of Moslems had decreased. At the beginning of war, prophet Muhammad  had  thousand warriors, but after this accident, prophet Muhammad had seven hundred warriors. This accident absolutely had decreased to the power of warriors.